Canonical correlations between morphological traits and yield components in dual‑purpose wheat - Carvalho, Ivan Ricardo; Souza, Velci Queiróz de; Nardino, Maicon; Follmann, Diego Nicolau; Schmidt, Denise; Baretta, Diego (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to identify canonical correlations between morphological traits and yield components in dual‑purpose wheat, under different cutting managements. The experiments were carried out in 2013 and 2014, under a complete block design, in a factorial arrangement with five genotypes (BRS Tarumã, BRS Umbu, BRS Figueira, BRS Guatambu, and BRS 277), four cutting managements (no cuts, one cut, two cuts, and three cuts), and three replicates. The canonical groups were established between morphological traits (group 1) and yield components (group 2). In group 1, number of tillers, diameter of the main stem and of the tillers, and number of fertile tillers were evaluated; in group 2, the number of grains per spike and of spikes per square meter, the mass of grains per spike and of a thousand grains, grain yield, and hectoliter weight were evaluated. The correlation between groups 1 and 2 depends on the adopted cutting management. The diameter of the main stem (in the managements without and with one cut), tiller diameter (two cuts), and the total number of tillers and of fertile tillers per plant (three cuts) should be prioritized for selection of superior genotypes as to grain yield and hectoliter weight.
Keywords: Triticum aestivum; multivariate analysis; cutting management; indirect selection